Corporate social responsibility disclosure in the annual reports of Malaysian companies: a longitudital study - Muhammad Jamil, Che Zuriana; Alwi, Kasumalinda; Mohamed, Rapiah (Universiti Utara Malaysia, 2003)
Corporate social responsibility (CSR) has a long history in both practices and research in advanced countries, mostly in Europe and the United States, However, in Malaysia, very few empirical studies are available on CSR practices. This study investigates and examines the development of CSR practice in Malaysian companies. The trend of CSR disclosure in annual reports for a five-year period from 1995 to 1999 has been reviewed to find out whether there are any changes in themes, locations or form of disclosure throughout the interval. The results show that the disclosure levels in Malaysia is considered low whereby less than 30 percent of companies studied made the CSR disclosure every year. The results also show that Malaysian companies prefer to disclose CSR in the Chairman's Statement, Financial Statement and Director's Report in the form of narrative information. Human resources, community involvement and environment were identified as the most popular themes. The findings reveal that the hotel, finance and construction sectors provide a higher percentage of CSR disclosure.